1999
DOI: 10.1097/00007632-199908010-00006
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Clinical and Magnetic Resonance Imaging Follow-Up Assessment of Patients With Lumbar Spinal Stenosis After Laminectomy

Abstract: Patients' perception of improvement had a much stronger correlation with long-term surgical outcome than structural findings seen on postoperation magnetic resonance imaging. Moreover, degenerative findings had a greater effect on patients' walking capacity than stenotic findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…Postoperative spinal computed tomographic or magnetic resonance imaging scans to assess surgery-induced spinal instability and the amount of bone removal were not performed routinely. However, it is known that the degree of radiologically confirmed decompression and evidence of instability are poorly related to the surgical outcome (6,9,10). The general composition, demographics, signs, symptoms, and surgical details in our patient population are comparable with those reported previously (1-4, 6-21, 23-26, 28-35).…”
Section: Limitations Of the Studysupporting
confidence: 66%
“…Postoperative spinal computed tomographic or magnetic resonance imaging scans to assess surgery-induced spinal instability and the amount of bone removal were not performed routinely. However, it is known that the degree of radiologically confirmed decompression and evidence of instability are poorly related to the surgical outcome (6,9,10). The general composition, demographics, signs, symptoms, and surgical details in our patient population are comparable with those reported previously (1-4, 6-21, 23-26, 28-35).…”
Section: Limitations Of the Studysupporting
confidence: 66%
“…5,8,12,14,2021,22 Yasar et al report the results of a prospective study of 125 patients with spinal stenosis with 2 year followup. The authors found no correlation between DOS and outcome of treatment, although the incidence of DS is not specified in the population.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, of the pain-related measures, only the Oswestry disability score was associated with depression. The Oswestry disability score [37,38] has been found to correlate with VAS pain assessments [56], and also a very strong correlation has been demonstrated between Oswestry scores and LSS patients' perception of improvement after surgery [57,58]. The Oswestry disability score seems to be a sensitive method for the detection of the subjective disability and the sense of everyday functioning of LSS patients.…”
Section: Discussionmentioning
confidence: 99%